Sintesis dan Karakterisasi Al-MCM-41 dari Kaolin: Pengaruh Konsentrasi HCl terhadap Struktur dan Kapasitas Adsorpsi Iodin - Abdullah, Affan Zein; Putri, Alisyah Ananda; Muljani, Srie; Nugraha, Reva Edra (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Al-MCM-41 can be synthesized using kaolin from Bangka Belitung without requiring additional sources of silica or aluminum. The process begins with calcination of kaolin to produce metakaolin, followed by HCl treatment for dealumination, which helps remove impurities and excess alumina. This step is crucial to achieve the optimal SiO₂/Al₂O₃ mole ratio, making the material effective as an adsorbent or catalyst. The hydrothermal process enhances silica polymerization and pore formation due to the strong electrostatic interactions between CTAB and silicate anions, increasing the pore size. The mesoporous structure and SiO₂/Al₂O₃ ratio of Al-MCM-41 are influenced by the CTAB concentration and the extent of dealumination through HCl treatment. In this synthesis, CTAB acts as a structure-directing agent, forming the hexagonal mesoporous framework, while HCl concentration regulates the removal of alumina from kaolin. To optimize the process, HCl concentrations of 2M, 4M, and 6M were tested to evaluate the extent of alumina and impurity removal. The 6M HCl treatment produced a SiO₂/Al₂O₃ ratio of 25.359, which aligns with the commercial Al-MCM-41 standard from ACS Material. Additionally, the iodine adsorption test demonstrated significantly higher adsorption capacity (653.14 mg/g) for Al-MCM-41 compared to kaolin (76.2 mg/g).